EFEKTIFITAS KONSELING KELOMPOK MODEL GESTALT UNTUK MENINGKATKAN RASA PERCAYA DIRI SISWA KELAS VIII 5 SMP NEGERI 2 SINGARAJA TAHUN PELAJARAN 2013/2014 - ., Kadek Agus Marthana Putra; ., Kadek Suranata, S.Pd.; ., Dra. Made Sulastri, M.Pd. (Jurnal Jurusan Bimbingan Konseling Undiksha, 2014)
Penelitian ini merupakan penelitian eksperimen. Populasi penelitian ini adalah siswa kelas VIII5 SMP Negeri 2 Singaraja. Sampel penelitian ditentukan dengan teknik purposive sampling, yaitu sampel yang dipilih didasarkan atas ciri-ciri tertentu yang di pandang mempunyai sangkut paut yang erat dengan ciri-ciri populasi yang telah diketahui sebelumnya. Sampel dalam penelitian ini adalah 6 orang siswa kelas VIII5 yang mengalami rasa percaya diri yang rendah. Rancangan penelitian ini adalah pretest-posttest-control group design. Metode pengumpulan data yang dipergunakan adalah kuesioner. Berdasarkan hasil analisis, ditemukan bahwa konseling kelompok model gestatl efektif untuk meningkatkan rasa percaya diri siswa, ini dilihat dari hasil analisis nilai thitung > ttabel dengan taraf signifikan 5% (0,568>0.207), berarti terjadi peningkatan rasa percaya diri siswa, ini terlihat dari hasil post test (723192). Berdasarkan analisis ini menunjukkan bahwa konseling kelompok model gestalt efektif digunakan untuk meningkatkan rasa percaya diri siswa.Kata Kunci : konseling kelompok model gestal, percaya diri. This study was an experimental study . The population was VIII5 grade students of SMP Negeri 2 Singaraja . The research sample was determined by purposive sampling technique , the sample is selected based on certain characteristics that in view of the close has nothing to do with the characteristics of the population that has been known previously . The sample in this study was 6 VIII5 graders who experienced low self-esteem . The study design was a pretest - posttest - control group design . The data collection method used was a questionnaire . Based on the analysis , it was found that group counseling gestatl effective models to improve the confidence of students , is seen from the results of the analysis of the value of t count > t table with a significance level of 5 % ( 0.568 > 0.207 ) , meaning an increase in self-confidence of students , is evident from the results post test ( 723 < 794 ) of the control class and experimental class ( 192-227 ) , the experimental group were given a gestalt model of group counseling is more effective than the control group treated in accordance with the counseling service in school without the gestalt model group , is visible from average value of the experimental group gain score is higher than the average value of the control group gain score ( 227 > 192 ) . Based on this analysis shows that the model group gestalt counseling effectively used to improve students' self-confidence.keyword : gestal model of group counseling, self-confidence